Human errors as functions of language / Patrick Tourchon - Tourchon, Patrick (Academy of Language Studies & UPENA, 2005)
Roman Jakobson extended the traditional communication diagram (which was just based on a sender, a message and an addressee) thanks to his studying speech abnormalities: namely, aphasia.Thus, the importance of context, contact and code occurred to him, bringing the number of relevant language functions up to six: referential, emotive, conative, phatic, metalingual and poetic. In this article, we also assume that deviant, off-standard samples of speech are more revealing than regular, standard ones. This leads us to pay attention to some more functions of language: suggestive, looping, and reverberating.